Bridging Institutional Theory and Public Sector Digitalization: The Case of SIPD - Rizqi Annisa; Wahyudin Nor (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Purpose: With this research, we want to better understand the opportunities and threats that local governments face as they work to integrate the Regional Government Information System (Sistem Informasi Pemerintahan Daerah/SIPD) for Accounting and Reporting. Method: Participants included members the provincial administration to the regencies of Banjar, Barito Kuala, Hulu Sungai Tengah, Hulu Sungai Selatan, Hulu Sungai Utara, Tabalong, Tapin, and Banjarmasin city, also the Financial and Development Supervisory Agency (BPKP) and the Audit Board of the Republic of Indonesia (BPK RI) participated in a qualitative case study that covered all of South Kalimantan Province. Data were collected through interviews and documentation. Findings: The research revealed a number of factors that challenge SIPD implementation, including concerns with the quality provided by systems and services, government format compliance with financial reports being less than 100%, data inaccuracies in its Administrative Module using system at both state and local levels, as well as technical problems also in the Administrative Module in delivering data to the Accounting and Reporting Module. Institutional theory describes that local governments persist in using SIPD despite existing constraints. Novelty/Value: This study offers new insights into accounting and reporting challenges under SIPD from the perspective of local governments and oversight institutions, emphasizing the need for system reliability, user adaptation, and regulatory alignment to support effective public financial management, based on findings reflected in BPK audit results.